THE EFFECT OF FIVE STOCK EXCHANGE MOVEMENT FROM 25 BIGGEST STOCK EXCHANGE IN THE WORLD TOWARD INDONESIA STOCK EXCHANGE PERIOD 2012 - 2017 - Mia Laksmiwati; Ivo Rolanda (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2019)
The IDX is inseparable from the influence of the global stock market, because globalization makes a country's economic system open. For Indonesia and several stock exchanges where the market capitalization is relatively small, optimism and pessimism of foreign stock investors is expected to greatly affect the movement of stock indexes. The fall of the global market has become a negative sentiment for the JCI movement. This study aims to determine the effect of the movement of five stock exchanges in the world on the ICI. In this study used multiple linear regression method using SPSS 25.0 statistical software. The results showed that SSE had no significant effect on CSPI while Nikkei 225, DJIA, S&P BSE Sansex, and STI had a significant effect on ICI during 2012 - 2017.